BRAND NAMES BASED ON ZOONYMS - Zhurayeva Zulaiho Shamsiddinovna; Ahmadaliyeva Sabokhan Muradovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article analyzes etymological and structural features of brand names based on zoonyms.